Predictive Factors for Efficacy of Dipeptidyl Peptidase-4 Inhibitors in Patients with Type 2 Diabetes Mellitus - Yagi, Shusuke (Diabetes Metab J, 2015)
BACKGROUND: Predictive factors for the efficacy of dipeptidyl peptidase-4 (DPP-4) inhibitors for lowering glycosylated hemoglobin (HbA1c) remain unclear in patients with type 2 diabetes mellitus. The aim of this study is therefore to clarify predictive factors of the efficacy of DPP-4 inhibitors for lowering HbA1c after 12 months of treatment. METHODS: A total of 191 consecutive type 2 diabetic patients (male sex 55%, mean age, 68.3±35.8 years), who had been treated with DPP-4 inhibitors for 12 months, were enrolled in this study and evaluated retrospectively. RESULTS: After 12 months of DPP-4 inhibitor treatment, random blood glucose level, and HbA1c level, decreased from 167±63 to 151±49 mg/dL (P<0.01), and from 7.5%±1.3% to 6.9%±0.9% (P<0.01) respectively, without severe side effects. Multiple regression analysis showed that predictors of DPP-4 inhibitor treatment efficacy in lowering HbA1c level after 12 months were a decrease in HbA1c level after 3 months of treatment, a high baseline HbA1c level, a low baseline body mass index, and the absence of coronary artery disease. CONCLUSION: Most suitable candidates for treatment with DPP-4 inhibitors are diabetics who are not obese and do not have coronary artery disease. In addition, long-term efficacy of DPP-4 inhibitors can be predicted by decrement of HbA1c after 3 months of treatment.